MODERN PEDAGOGICAL APPROACHES IN TEACHING ENGLISH AND THEIR EFFECTIVENESS - Ashuraliyeva Laylo Anvarjon qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article analyzes modern pedagogical approaches in teaching English and the effectiveness of using interactive methods and digital technologies in the educational process. It also highlights the importance of innovative methods in developing students’ communicative competence. The article provides recommendations for improving English language teaching in the education system of Uzbekistan.